Identification of Groundwater Using Geoelectric Method in Tobololo Village, West Ternate District Ternate City, North Maluku Province - Abdul Kadir Dahlan Arif; Wawan A.K Konoras; Letris Fara; Muhammad Djunaidi; Ibrahim Husni (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
Ternate City is the most densely populated area both demographically and building, this causes the need for clean water to increase, by looking at the geological structure of Ternate City which is most of the area is rock, of course it is an obstacle in itself in meeting the need for clean water The purpose of the activity is to obtain an overview of the availability and potential of groundwater that can be exploited in the study area, so that it can be used as an alternative to raw water supply planning. with indications that there is water at a depth of 160 to 190 meters, Based on the character pattern of the constituent rocks, there are sandstones, and tuff and subsurface contour patterns. Red, There are andesite rocks in the form of lava and brexi andesite. Dark Green – Light Green, There are clay rocks, this type of rock is included in impermeable rocks Orange Color: There are laharic brexi rocks, in this position it is very unlikely that water can be trapped, because laharic brexi is a lateral rock deposit, while clay is the opposite, which is characterized by impermeabl rocks, Blue Color, It is a puddle of surface water at a depth of 10 to 20 meters.